Implementasi Literasi Keuangan pada Anak Usia Dini Menurut Perspektif Ekonomi Islam Studi di RA Bustanul Ulum Lampung Tengah - Yulita, Nurma; Ekawati, Farida; Astuti, Sri Yuli (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2024)
This study aims to determine how the implementation of financial literacy education in early childhood is Islamic. Financial literacy in an Islamic context is a series of abilities and knowledge in terms of personal money management with the value of tawhid as the basis of all life practices. This research method uses qualitative descriptive with interview and observation techniques. The result of this study is to get the implementation of financial literacy education in RA Bustanul Ulum in general is to prioritize Tawhid and religious values, recognize the concept of money and carry out financial practices.with the main teaching material carried out by RA Bustanul Ulum is the Concept of Earning or the concept of income or better known as Mouslim Entrepreneur, the Concept of Saving or Savings / teachings not to be wasteful,  Sharing concept or sharing concept or known as Infaq, and Legalize prohibitions on bad practices in finance.